2015
DOI: 10.1038/nmat4483
|View full text |Cite
|
Sign up to set email alerts
|

Stress-stiffening-mediated stem-cell commitment switch in soft responsive hydrogels

Abstract: Bulk matrix stiffness has emerged as a key mechanical cue in stem cell differentiation. Here, we show that the commitment and differentiation of human mesenchymal stem cells encapsulated in physiologically soft (∼0.2-0.4 kPa), fully synthetic polyisocyanopeptide-based three-dimensional (3D) matrices that mimic the stiffness of adult stem cell niches and show biopolymer-like stress stiffening, can be readily switched from adipogenesis to osteogenesis by changing only the onset of stress stiffening. This mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
382
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 345 publications
(391 citation statements)
references
References 55 publications
9
382
0
Order By: Relevance
“…22,4448 These systems can be used to study how externally applied forces impact individual cells or multi-cellular tissue models. They also enable studies of how cell intrinsic forces regulate cell behaviour, often as a feedback from the resistance to these forces provided by the niche.…”
Section: Manipulating Mechanobiologymentioning
confidence: 99%
See 1 more Smart Citation
“…22,4448 These systems can be used to study how externally applied forces impact individual cells or multi-cellular tissue models. They also enable studies of how cell intrinsic forces regulate cell behaviour, often as a feedback from the resistance to these forces provided by the niche.…”
Section: Manipulating Mechanobiologymentioning
confidence: 99%
“…Additionally, substrate creep [G] and stress-stiffening [G] (Box 2) affect MSCs differentiation. 48,118 Unlike purely elastic systems, physical environments that exhibit viscoelastic behaviour allow cells to reversibly change their shape and volume in response to cues (FIG. 4B–C).…”
Section: Stem Cells Respond To Forcesmentioning
confidence: 99%
“…Although it has long been known that cells sense and respond to the elastic modulus of ECMs (11)(12)(13)(14), recent work has indicated an impact of nonlinear elasticity as well. Studies have found that the nonlinear elasticity of ECM regulates modes of cell motility (15) and differentiation of mesenchymal stem cells (16), alters how far cells are able to sense into the ECM (17), and enables long-range mechanical signaling between cells (18).…”
mentioning
confidence: 99%
“…The critical strain of the PIC hydrogels was increased by increasing the PIC polymer chain length, while the adhesion‐ligand density and the stiffness of PIC bulk hydrogel were kept constant. When cells were cultured in 3D PIC hydrogels, hMSCs preferred to differentiate into osteoblasts when the critical strain was increased, a process apparently mediated by microtubule‐associated protein DCAMKL 29. Taken together, these results highlight the strain‐stiffening property as an important element in fabricating 3D microenvironments.…”
Section: The Stem Cell Micronichementioning
confidence: 74%